Extreme fire spread events burn more severely and homogenize postfire landscapes in the southwestern United States - McFarland, Jessika R., author; Coop, Jonathan D., author; Balik, Jared A., author; Rodman, Kyle C., author; Parks, Sean A., author; Stevens-Rumann, Camille S., author; John Wiley & Sons Ltd, publisher (Colorado State University. Libraries, 2025)
Extreme fire spread events rapidly burn large areas with disproportionate impacts on people and ecosystems. Such events are associated with warmer and drier fire seasons and are expected to increase in the future. Our understanding of the landscape outcomes of extreme events is limited, particularly regarding whether they burn more severely or produce spatial patterns less conducive to ecosystem recovery. To assess relationships between fire spread rates and landscape burn severity patterns, we used satellite fire detections to create day-of-burning maps for 623 fires comprising 4267 single-day events within forested ecoregions of the southwestern United States. We related satellite-measured burn severity and a suite of high-severity patch metrics to daily area burned. Extreme fire spread events (defined here as burning > 4900 ha/day) exhibited higher mean burn severity, a greater proportion of area burned severely, and increased like adjacencies between high-severity pixels. Furthermore, increasing daily area burned also resulted in greater distances within high-severity patches to live tree seed sources. High-severity patch size and total high-severity core area were substantially higher for fires containing one or more extreme spread events than for fires without an extreme event. Larger and more homogenous high-severity patches produced during extreme events can limit tree regeneration and set the stage for protracted forest conversion. These landscape outcomes are expected to be magnified under future climate scenarios, accelerating fire-driven forest loss and long-term ecological change.
Keywords: area burned; burn severity; daily fire progression; extreme fire spread events; fast fires; forest resilience; landscape metrics